Real Time Responses: Front Line Educators’ View to the Challenges the Pandemic has Posed on Students and Faculty - Keown, Stacey; Carroll, Rob; Smothers, Moriah (Frontiers in Education, 2021)
After months of school closures, a variety of educators were surveyed with the goal of understanding their lived experience of teaching during a pandemic and the supports they needed to be successful during this challenge. The educators span different grade levels, school districts, and states. Their responses were illuminating for educational leaders when planning for a new school year. The purpose of this research brief was to collect real time responses from educators as they attempted to meet the varied challenges of educating during a pandemic. The questions focused on strengths needed by the educator, characteristics observed in successful students, and school supports that were helpful to gain successful outcomes. A variety of educators, spanning from kindergarten through high school, were surveyed. All participants were asked the same questions, and their responses were collected, coded, and organized around different educational leadership themes: teacher efficacy, school culture, and student resiliency. The goal of this research brief was to gain crucial information while educators were facing the pandemic and use their responses to frame a conversation for educational leaders as they plan for upcoming challenges they may face. From this research brief, characteristics of success begin to emerge. What does an educator need to focus on to be successful? What can we learn from our most successful students? What role can a school’s culture play, even when no one is there?